Penerapan Model Pembelajaran Kolaborasi dalam Meningkatkan Hasil Belajar Seni: Penelitian - Triyono, Triyono; Hartono, Hartono; Rokhman, Fathur; Wagiran, Wagiran (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Art education is essential, especially for promoting creativity among students. The purpose of this research is to investigate the use of a collaborative learning model to enhance student learning outcomes. The study used a quantitative approach with a pre-experimental one-group pretest-posttest design. The study included 20 pupils chosen via complete sampling. The collaborative learning approach, when used with fifth-grade primary school students, was shown to have a substantial positive impact on their learning outcomes, as evidenced by a significance value of 0. 000 < 0. 05. The application of this model is advised for use with fifth-grade primary pupils in art and culture topics, according to these findings.